How Companies are Responding to the Impact of Technology on the Future of Work - Shen, Qiwen (Transactions on Economics, Business and Management Research, 2024)
The rapid development of digital technologies, particularly artificial intelligence (AI), automation, and robotics, is profoundly reshaping the nature of work and organizations. This paper examines the impact of these technologies on the future of work by first introducing the theoretical foundations of technological disruption and human-AI collaboration. Automation and AI can perform not only routine manual and cognitive tasks but also more complex knowledge work, leading to predictions of widespread job displacement. However, digital technologies have also facilitated the emergence of new forms of work and employment, such as the platform economy and remote work. In the face of technological disruption, companies face both opportunities and challenges, needing to leverage advanced technologies to drive innovation, efficiency, and resilience while actively addressing the implications for the workforce and organizational change. By analyzing cases from DBS Bank and Stitch Fix, this paper demonstrates how enterprises optimize human-AI collaboration through workflow reengineering, job redesign, and workforce retraining during their digital transformations. DBS Bank has achieved efficiency gains and workforce skill upgrades through its "digital-to-the-core" strategy and the "DBS Skill Enhancement Education and Development (SEED)" program. Stitch Fix showcases the power of human-AI collaboration through its online personalized styling service that combines algorithmic recommendations with human judgment. Finally, this paper provides recommendations for organizational leaders, including making bold investments in workforce retraining and upskilling, optimizing job and process designs for human-AI collaboration, cultivating a culture that welcomes technological change, and emphasizing digital ethics and human-centered design.